2013
DOI: 10.1155/2013/383685
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Adipose-Derived Stem Cells: Fact or Fiction?

Abstract: Adipose-derived stromal cells (ASCs) are often referred to as adipose-derived stem cells due to their potential to undergo multilineage differentiation. Their promising role in tissue engineering and ability to modulate the immune system are the focus of extensive research. A number of clinical trials using ASCs are currently underway to better understand the role of such cell niche in enhancing or suppressing the immune response. If governable, such immunoregulatory role would find application in several cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 81 publications
(128 reference statements)
0
85
0
1
Order By: Relevance
“…Several recognized clinical studies have thus been performed to investigate the potential of BMSCs for the treatment of GVHD [15,[70][71][72][73]. In addition, both preclinical and clinical studies have been performed to evaluate the use of ASCs to prevent acute GVHD, as reviewed by Leto Barone et al [74]. Nonetheless, if ASCs are used for patients for immunomodulatory purposes, it is important to carefully assess the risk for the possibility of tumor formation connected with ASC-mediated suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Several recognized clinical studies have thus been performed to investigate the potential of BMSCs for the treatment of GVHD [15,[70][71][72][73]. In addition, both preclinical and clinical studies have been performed to evaluate the use of ASCs to prevent acute GVHD, as reviewed by Leto Barone et al [74]. Nonetheless, if ASCs are used for patients for immunomodulatory purposes, it is important to carefully assess the risk for the possibility of tumor formation connected with ASC-mediated suppression.…”
Section: Discussionmentioning
confidence: 99%
“…The niche of ASCs in adipose tissue has not been clarified. However, a number of recent studies indicate that it can be identified in adipose tissue vascularization process like shown by (Leto Barone et al 2013; Lin et al 2008a; Zimmerlin et al 2010). Zimmerlin et al (2010) identified the ASCs on outer adventitia of blood vessels.…”
Section: Phenotype and Niche Of Ascsmentioning
confidence: 92%
“…In addition, they are available in higher quantities and exhibit more cell homogeneity. Therefore, a number of studies have investigated the effects of AMSCs in tissue regeneration and immunomodulation [7,8].…”
Section: Introductionmentioning
confidence: 99%